Forest Resources of the Mackenzie River Basin, Northwest Territories - Robinson, J. M. (Polar Record, 1960)
The Mackenzie River is the seventh longest river in the world and with its tributaries drains a million sq. miles of northern Canada. Its drainage basin includes almost all of that portion of the District of Mackenzie lying south of the so-called “tree line”, two large sections of Yukon Territory and portions of the provinces of Saskatchewan, Alberta, and British Columbia. When flying from Fort Smith, lat. 60° N., to Inuvik near the Arctic Ocean it seems to be an endless expanse of swamp and tundra with almost no possibilities for logging, either now or in the future. Closer inspection, however, shows that there are forested areas capable of supplying timbers suitable for lumber and heavy construction, as well as poles for piling and mining timbers. It is with these forests that this article is primarily concerned.